Pemanfaatan Karbon Aktif dari Cangkang Kemiri sebagai Elektroda Superkapasitor - Kezia Kawulur; Heindrich Taunaumang; Sixtus Iwan Umboh; Cyrke Adfie Netty Bujung; Kamaruddin (Jurnal FisTa Fisika dan Terapannya, 2025)
The energy crisis is one of the major challenges facing the world today, triggered by over-reliance on fossil energy sources, rapid population growth, and the threat of climate change. One technology that attracts attention is supercapacitors. The purpose of this study was to determine the effect of carbon activation using KOH with varying concentrations on electrical conductivity as a supercapacitor electrode. By using dehydration method, carbonization at 500℃. The chemical activation process is treated with variations in KOH concentration of 6M, 7M, 8M with physical activation in a furnace at 750℃. The test results of conductivity and density values show that the comparison with the increase in KOH concentration results in an increase in conductivity of 0.1012 S/m, 0.1694 S/m, and 0.3282 S/m. Accompanied by a decrease in density of 9.8810 A/